Persepsi Masyarakat Batu Urip Terhadap Tradisi Mandi Kasai - Artiani Manullang; Sarkowi Sarkowi; Ira Miyarni Sustianingsih (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to describe the Batu Urip Community Perception of the Mandi Kasai Tradition in Batu Urip Village, North Lubuklinggau II District, Lubuklinggau City. The method used in this research is qualitative description. The steps used include: Observation, Interview, Questionnaire and Documentation. The results of this study contain the public's perception of the kasai bath tradition and the process of its implementation. Mandi kasai is a tradition that is used in marriage after the marriage contract. The community responds well and supports this tradition to be maintained and preserved so as not to lose it. The process of implementation from the beginning of the bridal procession, melanger, simburan bath, procession back home until the limit of this tradition is at Adam's marriage. Then the newlywed couple can continue sexual intercourse.